2016
DOI: 10.1590/0037-8682-0115-2016
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of and risk factors for leptospirosis in the City of Manaus, State of Amazonas, Brazil

Abstract: Introduction:Leptospirosis is caused by a bacterium of the genus Leptospira. This study aimed at investigating the seroprevalence of and risk factors for leptospirosis in humans in Manaus, State of Amazonas. Methods: Interviews were performed, and 1,000 blood serum samples were examined using a microscopic agglutination test. Results: Forty-three cases were positive; there were 10 serotypes, with coagglutination in 8 cases. The most frequently occurring serotypes were Icterohaemorrhagiae (20.7%), Cynopteri (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…A higher incidence in males of leptospirosis was also reported in Italy (14), Denmark (15) Korea (16), Fiji (17), Netherlands (18) and Japan (19). Furthermore, these results accord with studies performed in Brazil (11,20). It has also been described that a significant predominance of males with severe infections and a high prevalence of pulmonary manifestations (21).…”
Section: Discussionsupporting
confidence: 75%
“…A higher incidence in males of leptospirosis was also reported in Italy (14), Denmark (15) Korea (16), Fiji (17), Netherlands (18) and Japan (19). Furthermore, these results accord with studies performed in Brazil (11,20). It has also been described that a significant predominance of males with severe infections and a high prevalence of pulmonary manifestations (21).…”
Section: Discussionsupporting
confidence: 75%
“…Similar studies have been performed in Brazilian states close to French Guiana, namely, Amazonas and Para, that showed heterogeneous results and a high number of serogroups. 19,20 The most common reservoir for Leptospira is Rattus norvegicus. 15 In our study, when the information was available (N = 20), a contact with rodents was reported in 65% but because of the retrospective design of the study, the exposure rate remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent lack of concern could be caused by the presence of other endemic diseases such as malaria, Q fever, Amazonian toxoplasmosis, or dengue fever. 1,20,27,30 Thus, patients with mild form of the disease could be overlooked, leading to an underestimated burden of leptospirosis.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of human leptospirosis infection has mostly motivated studies either toward retrospectively confirmed cases (11)(12)(13)(14) or socially vulnerable communities (7,(15)(16)(17). Although providing crucial information on leptospirosis infection and clinical onset, such contributions may not be epidemiologically extrapolated to other endemic regions located in the more prosperous urban areas of some developing countries (18).…”
Section: Introductionmentioning
confidence: 99%